Kerkleiding in die een en twintigste eeu - Beukes, P. (Hervormde teologiese studies, 1997)
Church guidance in the twenty-first century. The view of church members relating to the roll of the church, roll overloading and different roll expectations have caused new thinking in the church leadership with a view on the twenty first century. This new thinking is further extended (enlarged) by the nature of post-modernism and various systems of thought. The mission of the church, the priesthood of the laity and the above mentioned factors have resulted in a specific spirituality, knowledge and various skills in regard to the church leaders with a view on the twenty first century.